Непубликуваните фикционални текстове (Васил Попович и Асен Христофоров) - Аретов, Николай (Poznańskie Studia Slawistyczne, 2020)
This paper deals with some texts from the archives of two authors from different periods. These texts were not published by the authors in their lifetime. The reason was not some kind of censorship, especially in the case of Vasil Popovich, who probably had some scruples dealing with events from the private life of his opponent Konstantin Jireček. Asen Hristoforov, a writer who was expelled from the University and sent to a labor camp, did not offer texts about his time in the labor camp for publishing. However, in this published texts there are hints about the repressions he suffered and about his disapproval of the communist regime. At the same time, there was a tension between his criticism and his attempt to partially accept the official perspective towards some events and political figures of Bulgarian communist past.